THE ANALYSIS OF ENGLISH SLANGS FOUND IN THE ANTMAN MOVIE - Kurnia Isnalisa Putri (Universitas Muhammadiyah Muara Bungo, 2022)
An educational program is a basic reference document for preparing the learning process. The teacher is the person who implements the program that has been determined. The educator's ability to use learning models in teaching can determine whether students are motivated to learn. Edutainment is a learning process designed to combine educational and entertainment content in harmony, making learning activities enjoyable. Entertaining learning is a learning model that includes a series of learning theories that involve students in learning activities that are fun and not boring. Some edutainment learning models that teachers can use are cooperative learning, multiple intelligence learning, PAKEM learning, quantum learning, and CTL (Contextual Teaching Learning )